Best value model for public private partnership infrastructure projects in Malaysia - Gambo, Muhammad Mustapha (2015)
The rapid human population growth rate coupled with the need for improved infrastructure project delivery has necessitated the participation of private sector for the procurement of such projects. Public Private Partnerships (PPP) is one such private sector driven procurement approach which has evolved to serve the growing demand for infrastructure development in Malaysia. However, the Value for Money (VfM) evaluative aspect of the PPP procurement form has faced criticism. Much of the criticism is directed to the PPP practice being riddled with issues identified as being related to the ineffective structuring of the private sector led project-specific Special Purpose Vehicle (SPV) to deliver VfM. Exploratory preliminary research findings indicate that there is a lack of overall long-term strategic focus by the SPV for delivering VfM objectives in PPP projects. Questionnaire survey data was obtained from a purposive sample of 48 public and private PPP practitioners in Peninsular Malaysia to determine the needed skills (core skills) and critical success factors (CSFs) required by the SPV to achieve their VfM objectives for PPP projects, and hence the successful delivery of PPP projects. The aim of the research is to develop a conceptual tool for delivering Best Value (BV) on PPP infrastructure projects. The notion of „skill sets‟ is used as a means to scope the capability necessary with respect to agreed planning targets on specific projects. A Best Value PPP conceptual framework is developed as a heuristic tool for managers which proposes the embedding of the VfM aligned PPP SPV organizational skills into the operational structure of the SPV and then effecting the SPV organizational strategic measures according to the four perspectives of the Balanced Scorecard performance measurement strategy with respect to the CSFs. Drawing on the understanding that VfM objectives are critical denominators for effective PPP project delivery, this research will influence the development of appropriate guidelines for the effective structuring of the SPV‟s to enable the delivery of enhanced VfM objectives in the form of BV for PPP concession projects.